2012
DOI: 10.3389/fnsys.2012.00017
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes of the corpus callosum in tinnitus

Abstract: Objectives: In tinnitus, several brain regions seem to be structurally altered, including the medial partition of Heschl's gyrus (mHG), the site of the primary auditory cortex. The mHG is smaller in tinnitus patients than in healthy controls. The corpus callosum (CC) is the main interhemispheric commissure of the brain connecting the auditory areas of the left and the right hemisphere. Here, we investigate whether tinnitus status is associated with CC volume. Methods: The midsagittal cross-sectional area of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…For instance, neural gamma synchronicity abnormalities, disturbed resting-state fMRI connectivity, as well as altered properties of IAPs have been observed consistently in patients with tinnitus 6972 and in patients with AVH in schizophrenia 1215,73–75 . In line with the present finding, the occurrence and severity of AVH have been related not only to more prominent IAPs 12,14,73 , but also to higher gamma-band synchrony between right and left auditory cortices and a reduced REA during dichotic listening 15,32 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, neural gamma synchronicity abnormalities, disturbed resting-state fMRI connectivity, as well as altered properties of IAPs have been observed consistently in patients with tinnitus 6972 and in patients with AVH in schizophrenia 1215,73–75 . In line with the present finding, the occurrence and severity of AVH have been related not only to more prominent IAPs 12,14,73 , but also to higher gamma-band synchrony between right and left auditory cortices and a reduced REA during dichotic listening 15,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there is a strong relationship between the structure and function of interhemispheric connectivity between the bilateral auditory areas and conscious auditory perception in general (Westerhausen et al, 2009, Steinmann et al, 2014b). This might explain why a relationship between interhemispheric auditory connectivity and auditory phantom perception is found not only in the context of AVH in schizophrenia, but also for example in the context of tinnitus (Diesch et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…The theory originates from research into tinnitus, which is an auditory precept of a tone without any corresponding external stimuli. Based on findings of hyper-synchrony between the auditory cortices (Eggermont, 2007), Diesch and colleagues suggested that stronger interhemispheric auditory pathways may facilitate the development and persistence of a positive feedback loop between tinnitus generators located in both hemispheres (Diesch et al, 2012). Studies using several modalities (fMRI, DTI, EEG) support the concept that altered connectivity between bilateral auditory areas via the corpus callosum (Fig.…”
Section: Major Hypotheses In the Current Literaturementioning
confidence: 99%
“…Despite its importance, there is a dearth of information regarding changes in interhemispheric functional connectivity in tinnitus patients. However, recent MRI studies have identified interhemispheric structural changes in tinnitus patients [ 16 19 ]. Diesch and colleagues demonstrated larger volume of the posterior CC splenium in tinnitus patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent MRI studies have identified interhemispheric structural changes in tinnitus patients [ 16 19 ]. Diesch and colleagues demonstrated larger volume of the posterior CC splenium in tinnitus patients [ 16 ]. Since many auditory fibers cross in the posterior part of the CC [ 20 ], the increased volume might be indicative of stronger interhemispheric connectivity.…”
Section: Introductionmentioning
confidence: 99%